BIG MEN OR CHIEFS? : rondel builders of neolithic europe. (OXBOW Books, 2018)
If there is a feature of the Central European Neolithic period that deserves increased attention of researchers and all those with interest in prehistory, it is circular architecture of the dimensions of many tens of metres, from which only negative imprints of the ditches and imprints of posts in the form of postholes or narrow trenches are preserved to this day. The reason is that it offers quite a different insight into the skills and interpersonal relationships of ancient societies that lived in Europe in the first half of the fifth millennium BC. The authors ask whether these structures, most often termed rondels, can be regarded as 'architecture of power' - the first clear evidence of thought-out power strategies of some individuals or their groups. Using anthropological terms - were they skilful and exceptional entrepreneurs with an ad hoc status (such as Big Men) living in egalitarian/segmented communities, or rather powerful Chiefs living in rank and hereditary based societies/chiefdoms?0.